Task Difficulty Modulates the Impact of Emotional Stimuli on Neural Response in Cognitive-Control Regions - Jasinska, Agnes J.; Yasuda, Marie; Rhodes, Rebecca E.; Wang, Cheng; Polk, Thad A. (Frontiers in Psychology, 2012)
Both heightened reactivity to emotional stimuli and impaired cognitive control are key aspects of depression, anxiety, and addiction. But the impact of emotion on cognitive-control processes, and the factors that modulate this impact, are still not well understood. We examined the effects of threat and reward distracters on the neural correlates of cognitive control using functional MRI (fMRI) and the Multi-Source Interference Task (MSIT). Behaviorally, subjects were slower and less accurate on the more demanding incongruent trials compared to the easier congruent trials. In addition, both threat and reward distracters significantly impaired the speed of responding on incongruent trials relative to the no-distracter condition. At the neural level, we used the incongruent – congruent contrast to functionally define four cognitive-control regions of interest (ROIs): anterior cingulate cortex (ACC), left and right inferior frontal gyrus (IFG)/insula, and right dorsolateral prefrontal cortex (DLPFC). A repeated-measures analysis of variance on the extracted contrast values in these ROIs indicated a significant interaction of stimulus salience and task difficulty on the neural response in cognitive-control regions. Specifically, threat distracters significantly decreased the response in cognitive-control regions on incongruent trials, whereas they significantly increased that response on congruent trials, relative to the no-distracter condition. Exploratory analyses of the amygdala response showed a similar interaction of stimulus salience and task difficulty: threat distracters significantly decreased the amygdala response only on incongruent trials. Overall, our results suggest that the impact of emotional distracters on the neural response in cognitive-control regions as well as in the amygdala is modulated by task difficulty, and add to our understanding of the factors that determine whether emotion enhances or impairs cognition.